EDUKASI PENCEGAHAN STUNTING MELALUI MAKANAN PENDAMPING ASI BERBASIS PANGAN LOKAL DAN TEKNOLOGI PENGOLAHANNYA DI ORW 09 KELURAHAN TAMALANREA KOTA MAKASSAR - Wiyani, Lastri; Aladin, Andi; Rasyid, Rismawati; Wahyuni, Arinda; Azzahra, Qanitati; Nirma, Nirma; Nurhalifa, Nurhalifa (Universitas Mataram, 2024)
One of the problems of malnutrition that needs serious attention is stunting. This problem is so important that it requires proper handling. Stunting is a condition where a child's growth is stunted or fails. This is due to malnutrition that occurs early in a child's life. Stunting can affect a child's health and intelligence level. One way to prevent stunting is the provision of nutritious complementary foods (MPASI). Education can be done by providing knowledge about stunting and complementary feeding to the community, especially mothers. The purpose of this service is to provide an understanding of the importance of preventing stunting for children under five, as well as to provide an understanding that complementary foods can be made from local food ingredients that are nutritious and proper processing. The method used begins with a survey, the implementation of activities in the form of counseling using audiovisuals, demonstrations of making complementary foods and discussions. The results of the program showed that the community understands what stunting is, how to prevent stunting, what complementary food is, the right time and frequency to give complementary food, the stages of giving complementary food, local food to make complementary food, and advice on how to make easy and nutritious complementary food. Examples of complementary foods that can be given are purple sweet potato mud cake which is rich in antioxidant compounds and shrimp-fish rice nuggets which are rich in protein and fatty acids. Based on the results of these activities, education with counseling using audiovisuals proved effective in increasing mothers' understanding of stunting and complementary feeding. The processing of complementary food can be done simply using local food sources by paying attention to nutritional value, selection of ingredients, handling and processing processes. It is suggested that in the next stage, regular monitoring through the local Posyandu is needed to continue to educate, provide nutritious food and immunize residents according to regulation set by the government.